How to #LoveTheReef - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2016)
An infographic of practical tips and useful information about protecting the Great Barrier Reef. The How to #LoveTheReef infographic comes in JPG format only in both portrait and landscape orientation.
Keywords: Graphics; People and the Reef; Climate change; Water quality; Coastal communities; Reef-wide